Evolutionary trace analysis of a zinc metalloenzyme – alcohol dehydrogenase / Sakinah Jamil - Sakinah, Jamil (2012)
Molecular evolution is the study of the evolutionary patterns and processes of nucleic acids and proteins to understand the phylogenetics, population genetics, biogeography, and other areas of research at the DNA, RNA and protein levels of the biological organization. Evolutionary trace method is a technique to identify evolutionary important residues and their positions in a group of protein alignment. In this study, the zinc metalloenzyme alcohol dehydrogenases (ADH) of the eukaryote Mus musculus (mouse) was used as the sequence of interest against 48 other bacteria species. BLAST was used to identify the 48 bacteria species with the closest ADH sequences to the Mus musculus ADH. Multiple sequences alignment was done in order to construct the phylogenetic tree to view the evolutionary relationship of the sequences. Partitions on the Cladogram were created to trace back to where the organisms branch off pointing to a common ancestor. Each partition was then split into smaller groups to identify similar species in the family. 29.8% of the residues in the first partition were fully conserved whilst another 47.8% of the active site residues were fully conserved.